2010
DOI: 10.5194/hess-14-2193-2010
|View full text |Cite
|
Sign up to set email alerts
|

The role of climatic and terrain attributes in estimating baseflow recession in tropical catchments

Abstract: Abstract. The understanding of low flows in rivers is paramount more than ever as demand for water increases on a global scale. At the same time, limited streamflow data to investigate this phenomenon, particularly in the tropics, makes the provision of accurate estimations in ungauged areas an ongoing research need. This paper analysed the potential of climatic and terrain attributes of 167 tropical and sub-tropical unregulated catchments to predict baseflow recession rates. Daily streamflow data (m 3 s −1 ) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 34 publications
10
61
0
Order By: Relevance
“…The associated abandonment of pastures and agricultural fields allowed secondary forests to develop over increasingly large areas as time progressed (Thomlinson et al, 1996;Grau et al, 2003;Helmer, 2004;Parés-Ramos et al, 2008;Fig. 1 1955 1960 1965 1970 1975 1980 1985 1990 1995 documented, both in terms of its expansion over time, and forest composition and structure Chinea and Helmer, 2003;Grau et al, 2003).…”
Section: Study Areamentioning
confidence: 99%
“…The associated abandonment of pastures and agricultural fields allowed secondary forests to develop over increasingly large areas as time progressed (Thomlinson et al, 1996;Grau et al, 2003;Helmer, 2004;Parés-Ramos et al, 2008;Fig. 1 1955 1960 1965 1970 1975 1980 1985 1990 1995 documented, both in terms of its expansion over time, and forest composition and structure Chinea and Helmer, 2003;Grau et al, 2003).…”
Section: Study Areamentioning
confidence: 99%
“…Commonly at least the first 5 days of periods with declining streamflow are removed from analysis (e.g. Szilagyi and Parlange, 1998;Peña-Arancibia et al, 2010), but studies can also be found that eliminated an interval between 1 and 10 days (Zecharias and Brutsaert, 1988a;Vogel and Kroll, 1992;Parlange et al, 2001;Malvicini et al, 2005;van Dijk, 2010;Wang and Cai, 2010). Singh and Stall (1971) divided the declining hydrograph at the inflection point and analyzed only the latter part to reduce influence of surface flows at the beginning of recession.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the variety of adaptations of the original method by Brutsaert and Nieber (1977), these different RAMs have also been applied to various catchment types with different catchment areas and different physiographic, geological, and climatic characteristics including in humid (Troch et al, 1993), in tropical (Peña-Arancibia et al, 2010), in semi-arid (Mendoza et al, 2003;Ajami et al, 2011) and sub-artic (Lyon et al, 2009) regions. Furthermore methods have been applied to catchments with different land use characteristics such as forested catchments (Parlange et al, 2001), deforested catchments (Malvicini et al, 2005), mountainous catchments (Zecharias and Brutsaert, 1988a;Teuling et al, 2010) and also explicitly to small catchments (Krakauer and Temimi, 2011) and to a lowland plain with a deep aquifer .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have determined or assumed that, at least well after rain events, b = 1 to acceptable accuracy, so that only one parameter, a, must be estimated from measured streamflow (e.g. Vogel and Kroll, 1992;Brandes et al, 2005;Eng and Milly, 2007;van Dijk, 2010). In this case the reciprocal of a is the recession timescale τ , corresponding to the ratio −Q/Q.…”
Section: Introductionmentioning
confidence: 99%